Economic study of Tanjung Manis Airport, Sarawak, Malaysia / Mohd Irhasman Inggal - Inggal, Mohd Irhasman (2020)
Air transportation is essential to most of the people across the globe. lt helps people to travel all over the world in a short time period. This paper is about the economic study of Tanjung Manis Airport, Sarawak, Malaysia. Tanjung Manis Airport is a small airport located in Tanjung Manis that serve Mukah and Sarikei Division, Sarawak. The aim of this paper is to study ways for the sustainability of operation of Tanjung Manis Airport. There are three (3) research objectives had been developed to meet the aim; to identify operation cost, maintenance cost & revenue of Tanjung Manis Airport; to study ways to lower operating and maintenance cost of Tanjung Manis Airport; and to approach sustainable operations of Tanjung Manis Airport by investigating ways to increase airport's revenue.